STRATEGIES FOR ORGANIZING VISUAL ARTS LESSONS (Conferencea, 2024)
The organization of visual arts classes plays an important role in monitoring students' creative development and creative learning environments. The course examines the development of effective strategies for organizing visual arts, physical space, content, curriculum planning, and classroom management. By implementing best practices in classroom organization, teachers can create engaging and supportive environments that foster students' creative learning, inspire creativity, and encourage a lifelong appreciation for the arts.